2021
DOI: 10.1007/s00132-021-04088-7
|View full text |Cite
|
Sign up to set email alerts
|

Protheseninfektionen und die zunehmende Bedeutung psychologischer Komorbiditäten

Abstract: Zusammenfassung Hintergrund Die periprothetische Gelenkinfektion (PJI) ist eine gefürchtete Komplikation in der Orthopädie und Unfallchirurgie. Ein potenzieller Anstieg an PJI-Diagnosen, insbesondere in Verbindung mit psychologischen Komorbiditäten, kann zu einer besonderen Herausforderung für Akteure im Gesundheitswesen werden. Bisher ist die Prävalenz für Deutschland unbekannt. Dies erschwert es, den zukünftigen Behandlungsbedarf abzuschätzen und Entwicklungen vorherzusehen, die d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Likewise, septic revisions due to PJI increased by over 50% within the last decade [ 6 , 7 ]. Similarly, an incidence of PJI between 23.5 and 27.8 per 100,000 inhabitants in Germany was detected and showed constant growth [ 8 ]. Both types of infection require long and intense therapy, usually a combination of multiple revision surgeries and long-term antibiotic therapy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, septic revisions due to PJI increased by over 50% within the last decade [ 6 , 7 ]. Similarly, an incidence of PJI between 23.5 and 27.8 per 100,000 inhabitants in Germany was detected and showed constant growth [ 8 ]. Both types of infection require long and intense therapy, usually a combination of multiple revision surgeries and long-term antibiotic therapy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 37 Recently, also raising numbers of psychological comorbidities over the years have been shown for PJI patients, whereby the authors concluded that interdisciplinary collaboration is warranted and a psychologists should be included in the management. 11 In light of the presented findings, routine geriatric screening assessment should be considered. Further, the high number of geriatric infection patients (72.2%) emphasizes that geriatric physicians should be included as part of the PJI treatment team.…”
Section: Discussionmentioning
confidence: 88%
“… 10 Periprosthetic joint infection (PJI) is a dreaded complication in orthopaedics and trauma surgery with an incidence of 24/1 000 000 inhabitants in Germany. 11 Hence, an increasing percentage of older patients with bone and joint infection is expectable.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] According to the recent literature, the overall mortality rate of patients suffering from PJI is 3.2 to 3.7 times higher than of those without joint infection. 3,16 A database search revealed a one-year mortality rate of 4.22% after PJI of the hip and a five-year mortality as high as 21%. 17 A recent study showed that patients with PJI have an even higher risk for in-hospital mortality than those having interventional coronary procedures, cholecystectomy, kidney transplant, or carotid surgery.…”
Section: Introductionmentioning
confidence: 99%